Chemical synthesis, docking studies and biological effects of functionalized 1,3-diaryl-2-propen-1-ones on human colon cancer cells (Bangladesh Journal of Pharmacology, 2015)
A series of 1, 3-diaryl-2-propen-1-ones was synthesised in order to obtain a new type of anticancer drug, designed with hybrid features to inhibit colon cancer activated receptor. Based on computational modelling and docking studies, potential inhibitors were synthesised and their biological activity evaluated. The structures of newly synthesized compounds were confirmed by 1HNMR, 13CNMR and Mass spectrometry. All analogues were evaluated for in vitro cytotoxicity against human colon (caco-2) cancer cell lines. Compounds 1b, 1f-1h, and 2i showed significant cytotoxicity. Chalcones 1b, 1f and 1g were identified as the most potent and selective anticancer agents with IC50 values